Increased psoriasis frequency in patients with familial Mediterranean fever. (2nd January 2018) - Erden, Abdulsamet; Batu, Ezgi Deniz; Seyhoğlu, Emrah; Sari, Alper; Sönmez, Hafize Emine; Armagan, Berkan; Demir, Selcan; Bilgin, Emre; Kilic, Levent; Karadag, Omer; Akdogan, Ali; Bilginer, Yelda; et al.
Abstract: Objective: Familial Mediterranean fever (FMF) is a periodic fever syndrome caused by MEFV mutations. FMF may be associated with psoriasis in some cases. The prevalence of psoriasis in the normal Turkish population is 0.42%. We aimed to investigate the prevalence of psoriasis among FMF patients and their relatives. Methods: FMF patients followed at Hacettepe University Adult and Pediatric Rheumatology Departments between January and August 2016 were included. FMF patients/their relatives were accepted to have psoriasis if the diagnosis was made by a dermatologist. Results: A total of 351 FMF patients (177 adults; 174 children) were included. The median (min–max) age of adult and pediatric patients was 35 (19–63) and 10 (2–18) years, respectively. Thirteen (3.7%) FMF patients (11 adults, 2 children) had psoriasis. Psoriasis was more common in adult than pediatric patients ( p = 0.02). Psoriasis was present in 22 (12.4%) of adult and 9 (5.2%) of pediatric patients' relatives ( p = 0.023). The frequency of psoriasis in ≥1 relatives of FMF patients was found to be 8.8%. Abdominal pain and fever were significantly higher, and arthralgia, arthritis, pleural chest pain, and pericarditis were significantly less frequent in the pediatric group than in adults ( p < 0.05). Conclusion: Psoriasis was more common in FMF patients than in the normal population. Thus, FMF patients should be questioned and carefully examined for psoriasis lesions and psoriasis family history. Prospective multicenter studies may be important to find the incidence of psoriasis in FMF.